The constitutional court function of the Indonesian state concerning system for the implementation impeachment of the president and/or vice president - H Muhamad Rezky Pahlawan MP (Jurnal Hukum Volkgeist, 2020)
Impeachment is an accusation or indictment of the President or another country's high officials from his position. Impeachment is not new in the history of Indonesian constitution, but the change in the Constitution has caused a change in the constitutional system as well as related to the mechanism of the dismissal of the President and / or Vice President. how is the Impeachment reviewed globally, the history of impeachment in Indonesia and the implementation of impeachment in other countries, the impeachment process of the president according to the 1945 Constitution of the Republic of Indonesia. The process of impeachment in Indonesia after changing the constitution goes through three stages, namely impeachment in the House of Representatives, the Court The Constitution, and the People's Consultative Assembly. Keywords: Impeachment, Constitutional Court, Government